Photon Decay Hypothesis in Cosmological Models: Revisiting Primordial Nucleosynthesis Constraints for Alternative Universe Origin Theories - Vijayan, Deepthi (Journal of Research in Science and Engineering, 2025)
This paper critiques existing models of the universe, highlighting their limitations and proposing a new model based on the concept of photon decay. The proposed model challenges the Big Bang theory, suggesting that the universe is boundless but finite and is not expanding. Instead, it proposes a continuous decay of photons into smaller particles, which has significant implications for understanding cosmic phenomena, including redshifts and cosmic microwave background radiation. This theoretical framework offers an alternative perspective on cosmology, emphasizing the need for further exploration and validation.